Detection of β-thalassemia mutations using a multiplex amplification refractory mutation system assay - Mirasena S. (2014)
We developed two sets of a multiplex amplification refractory mutation system (M-ARMS) assay to identify specific β-thalassemia (β-thal) mutations that are common in Thailand. The first one was for the detection of mutants with codon 17 (A>T), IV S-I-1 (G >T)), codons 41/42 (-TCT T) and codons 71/72 (+A), while the second one was for the -87 (C>A), -28 (A>G) and IVS-II-654 (C>T). Application of the proposed assay to 282 persons with β-thal trait revealed a positive result in 276 cases (97.8%). There were 258 cases (91.5%) positive for the set 1 M-ARMS assay and 18 cases (6.4%) were positive for set 2. Six cases (2.2%) were negative for both sets 1 and 2, and were further characterized by DNA sequencing. The mutations detected by the set 1 M-ARMS assay were 113 cases (40.1%) of codons 41/42, 95 (33.7%) of codon 17, 41 (14.5%) of IVS-I-1 and nine cases (3.2%) of codons 71/72, while by set 2 there were 12 cases (4.2%) of -28, four cases(1.4%) of -87 and two cases (0.7%) of IVS-II-654. Mutations undetectable by M-ARMS assay were two cases of codons 27/28 (+C), one case of codon 35 (C>A), one of codon 43 (G>T), one of -31 (A>G) and one of IVS-I-5 (C>G). The M-ARMS assay proved to be a valuable tool for the analysis of β-thal mutations. The method is robust, accurate, simple, speedy and cost-effective. The application of this assay will facilitate genetic counseling and prenatal diagnosis for severe thalassemia in high-risk pregnancies. Copyright © Informa Healthcare USA, Inc.